Progressive Resistance Training for Improving Health-Related Outcomes in People at Risk of Fracture: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 2 (26th December 2020) - Ponzano, Matteo; Rodrigues, Isabel B; Hosseini, Zeinab; Ashe, Maureen C; Butt, Debra A; Chilibeck, Philip D; Stapleton, Jackie; Thabane, Lehana; Wark, John D; Giangregorio, Lora M
Abstract: Objective: Osteoporosis clinical practice guidelines recommend exercise to prevent fractures, but the efficacy of exercise depends on the exercise types, population studied, or outcomes of interest. The purpose of this systematic review was to assess the effects of progressive resistance training (PRT) on health-related outcomes in people at risk of fracture. Methods: Multiple databases were searched in October 2019. Eligible articles were randomized controlled trials of PRT interventions in men and women ≥50 years with low bone mineral density (BMD) or fracture history. Descriptive information and mean difference (MD) and SD were directly extracted for included trials. A total of 53 studies were included. Results: The effects of PRT on the total number of falls (incidence rate ratio [IRR] = 1.05; 95% CI = 0.91 − 1.21; 7 studies) and on the risk of falling (risk ratio [RR] = 1.23; 95% CI = 1.00 − 1.51; 5 studies) are uncertain. PRT improved performance on the Timed "Up and Go" test (MD = −0.89 seconds; 95% CI = −1.01 to −0.78; 13 studies) and health-related quality of life (standardized MD = 0.32; 95% CI = 0.22–0.42; 20 studies). PRT may increase femoral neck (MD = 0.02 g/cm 2 ; 95% CI = 0.01–0.03; 521 participants, 5 studies) but not lumbar spine BMD (MD = 0.02 g/cm 2 ; 95% CI = −0.01–0.05; 4 studies), whereas the effects on total hip BMD are uncertain (MD = 0.00 g/cm 2 ; 95% CI = 0.00–0.01; 435 participants, 4 studies). PRT reduced pain (standardized MD = −0.26; 95% CI = −0.37 to −0.16; 17 studies). Sensitivity analyses, including PRT-only studies, confirmed these findings. Conclusion: Individuals at risk of fractures should be encouraged to perform PRT, as it may improve femoral neck BMD, health-related quality of life, and physical functioning. PRT also reduced pain; however, whether PRT increases or decreases the risk of falls, the number of people experiencing a fall, or the risk of fall-related injuries is uncertain. Impact: Individuals at risk of fractures should be encouraged to perform PRT, as it may have positive effects on femoral neck BMD, health-related quality of life, physical functioning, and pain, and adverse events are rare. Lay Summary: Exercise is recommended for people at risk of osteoporotic fractures. Our study showed that progressive resistance training improves physical functioning, quality of life, and reduces pain. The effects of progressive resistance training on the risk of falling are unclear. Adverse events are rare, and often minor (eg, soreness, pain, musculoskeletal injury). Considering the benefits and safety, people at risk of fractures should engage in progressive resistance training interventions.